Barrio África Mía en Quito: mujeres, cuerpo-territorio y racismo ambiental - Rocío Vera Santos (Nuevo mundo - Mundos Nuevos, 2025)
Based on an ethnographic study, biographical narratives of the founding women of the África Mía neighborhood in Quito, and academic and media publications, this article examines a concrete case of urban segregation, violence, and environmental racism, alongside examples of territoriality, agency, and resilience among the women of África Mía. The neighborhood consists of 14 Black women, single mothers, and domestic workers. Its establishment involved processes of economic agency, entrepreneurship, and cultural expression through a dance group. For decades, the neighborhood has faced severe environmental pollution issues.